De l’éducation religieuse à l’endoctrinement : enseignement et manipulation des enfants en Espagne à l’époque moderne - Emmanuelle Buvat-Bruyère (E-Spania)
This study tends to show the central place of the child in the Spanish educational policy in the modern period. As elementary education combines instruction and religion, it is worth wondering how the christian doctrine has successfully imposed itself from the Tridentine period involving the child in a more global indoctrination process which concerns the whole society.